2018
DOI: 10.3892/mmr.2018.9324
|View full text |Cite
|
Sign up to set email alerts
|

Emodin alleviates CCl4‑induced liver fibrosis by suppressing epithelial‑mesenchymal transition and transforming growth factor‑β1 in rats

Abstract: Liver fibrosis is a chronic disease that exhibits a complicated pathophysiology. It is characterized by the deposition of the extracellular matrix. Emodin, an active constituent isolated from rhubarb, has antibacterial, immunosuppressive and anti-inflammatory effects. In the present study, the mechanism through which emodin alleviates liver fibrosis in rats was investigated. A rat model of liver fibrosis was generated by administering CCl4 via subcutaneous injection twice a week for 12 weeks. Emodin or sodium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 41 publications
(38 reference statements)
1
26
0
Order By: Relevance
“…Zhao's research indicated that the mechanism of emodin against liver fibrosis was partially related to a reduction in the infiltration of Gr1hi monocytes [ 117 ]. Moreover, emodin also protected against liver fibrosis and HSC activation by reducing TGF- β 1 and Smad4 expression and inhibiting tissue inhibitor of metalloproteinases-1 (TIMP-1) expression, and epithelial-mesenchymal transition [ 118 120 ]. In addition, 25 and 100 mg/kg rhein inhibited liver fibrosis induced by CCl 4 /ethanol in rats, which possibly benefited from antioxidant and anti-inflammatory activities of rhein.…”
Section: Quinonesmentioning
confidence: 99%
“…Zhao's research indicated that the mechanism of emodin against liver fibrosis was partially related to a reduction in the infiltration of Gr1hi monocytes [ 117 ]. Moreover, emodin also protected against liver fibrosis and HSC activation by reducing TGF- β 1 and Smad4 expression and inhibiting tissue inhibitor of metalloproteinases-1 (TIMP-1) expression, and epithelial-mesenchymal transition [ 118 120 ]. In addition, 25 and 100 mg/kg rhein inhibited liver fibrosis induced by CCl 4 /ethanol in rats, which possibly benefited from antioxidant and anti-inflammatory activities of rhein.…”
Section: Quinonesmentioning
confidence: 99%
“…In recent research, emodin relieved the severity of fibrosis via downregulation of TGFβ 1 -Smad signaling. 43 Additionally, emodin relieved fibrosis symptoms via inactivation of TGFβ 1 -Smad signaling. 44 Our study was consistent with these results.…”
Section: Discussionmentioning
confidence: 99%
“…Besides goji berry-derived ZD, other active compounds have been isolated from TCM herbs, and their effects on liver disease were investigated. These include berberine (Huanglian) [20, 21], emodin (Dahuang) [22], and gastrodin (Tianma) [23, 24]. Although few studies assessing the benefits of ZD cover a wide range of liver conditions.…”
Section: Introductionmentioning
confidence: 99%